Fiscal Policy Through Time-Varying Tax Rates : If and How - Kaufman, Martin (IMF Working Papers; Working Paper ;, 2000)
This paper investigates if there are circumstances where time-varying tax rates could improve welfare and whether such policy can effectively be implemented in practice. While, in principle, variable taxes could improve welfare in some cases, the paper highlights the very particular circumstances that need to prevail. With liquidity constraints, a consumption-tax break is in a better footing to boost consumption and welfare than an income-tax break. A hike in consumption taxes can also be used to restrain consumption and improve welfare under time-consistency problems induced by hyperbolic discounting. However, variable taxes are subject to serious implementation problems fettering their use.